Pelatihan Desain Layout Buku Monograf dengan Canva untuk Guru dan Dosen pada PPMULTINDO - Cahaya Jatmoko; Sindhu Rakasiwi; Feri Agustina; Daurat Sinaga; Heru Lestiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
In the midst of the demand to actively publish scientific papers, the ability to design is a significant added value for teachers and lecturers. This report outlines a monograph book layout design training with Canva held for academics at PPMULTINDO. The main purpose of this activity is to provide practical skills so that participants can independently produce professional book layouts. This training uses an interactive workshop method, where participants are guided from the introduction of Canva's features, the application of design principles, to the practice of preparing layout chapters by chapter. As a result, participants demonstrated a significant improvement in their ability to operate Canva for publication design needs. They are able to produce a structured, consistent, and visually appealing layout. Thus, this training has succeeded in becoming a practical solution for academics to efficiently improve the visual quality of their monograph books